Developing a one‐stop tinnitus service: outcomes of a joined up management strategy: a retrospective observational cohort study. Issue 1 (28th August 2015) - Farr, Matthew R. B.; Moraleda Deleito, Javier; Xu, Yanmin; Ray, Jaydip
Abstract: Rationale, aims and objectives: The pressure to deliver quality care with finite resources means that dealing with single‐symptom conditions like tinnitus in an efficient and individualized manner has never been more important. Both primary and secondary care practitioners have an obligation to explore efficient delivery of simple management pathways. Commissioners of health care are in a unique position to affect evidence‐based strategic change in the management of uncomplicated tinnitus. This study is an attempt to explore one such option. We present the outcomes of a tinnitus patient pathway designed for one‐stop management, thereby minimizing unnecessary additional appointments. Method: A retrospective observational cohort study of 452 patients referred to a NHS one‐stop tinnitus clinic from 2008 to 2012. Clinical care guided was through the use of a structured approach to history taking, neurotological examination and management. Results: 294 out of 452 (65%) of patients referred had unilateral tinnitus. The most common associated complaints were hearing loss (387/452, 86%) and hyperacusis (329/452, 73%). 210 (46%) of patients had their presenting complaint dealt with in a single clinic visit. Conclusion: A structured system for referral and management of tinnitus within the health system ensures patients have timely access to evidence‐based investigation and treatment. A consistent approach to imaging aimed at identifying retrocochlear pathology can benefit patients through early diagnosis of central pathology and the reassurance provided by a negative scan.